A Machine Learning Approach to Predicting New‐onset Depression in a Military Population. Issue 3 (12th February 2021) - Sampson, Laura; Jiang, Tammy; Gradus, Jaimie L.; Cabral, Howard J.; Rosellini, Anthony J.; Calabrese, Joseph R.; Cohen, Gregory H.; Fink, David S.; King, Anthony P.; Liberzon, Israel; Galea, Sandro
Abstract : Objective: Depression is one of the most common mental disorders in the United States in both civilian and military populations, but few prospective studies assess a wide range of predictors across multiple domains for new‐onset (incident) depression in adulthood. Supervised machine learning methods can identify predictors of incident depression out of many different candidate variables, without some of the assumptions and constraints that underlie traditional regression analyses. The objectives of this study were to identify predictors of incident depression across 5 years of follow‐up using machine learning, and to assess prediction accuracy of the algorithms. Methods: Data were from a cohort of Army National Guard members free of history of depression at baseline ( n  = 1951 men and 298 women), interviewed once per year for probable depression. Classification trees and random forests were constructed and cross‐validated, using 84 candidate predictors from the baseline interviews. Results: Stressors and traumas such as emotional mistreatment and adverse childhood experiences, demographics such as being a parent or student, and military characteristics including paygrade and deployment location were predictive of probable depression. Cross‐validated random forest algorithms were moderately accurate (68% for women and 73% for men). Conclusions: Events and characteristics throughout the life course, both in and outside of deployment, predict incident depression in adulthood among military personnel. Although replication studies are needed, these results may help inform potential intervention targets to reduce depression incidence among military personnel. Future research should further refine and explore interactions between identified variables. HIGHLIGHTS: In a cohort study of U.S. Army National Guard personnel, we found that stressors and traumas such as emotional mistreatment and adverse childhood experiences, demographics such as being a parent or student, and military characteristics including paygrade and deployment location were predictive of new‐onset depression. Cross‐validated random forest algorithms were moderately accurate for predicting depression. Among military personnel, events and characteristics throughout the life course—in and outside of deployment—predict new‐onset depression in adulthood.